Enhanced performance of UV photodetector based on ZnO nanorod arrays via TiO2 as electrons trap layer. (September 2022) - Yin, Zihan; Shan, Yujie; Yu, Mingyan; Yang, Lun; Song, Jiaming; Hu, Peng; Teng, Feng
Abstract: As a commonly used substrate and matrix material in the construction of high performance ultraviolet photodetector, ZnO nanorod arrays have attached much attention due to their efficiency electron transmission channels and high stability. However, they also have the problem of slow response speed inevitably. In this work, TiO2 /ZnO nanorod arrays heterojunction structure was prepared and used to construct ultraviolet photodetector. The obtained heterojunction photodetector has a higher on/off ratio (>1000) and shorter rise/decay time (6.1/3.7 s) compared with that of photodetector based on ZnO nanorod arrays (on/off ratio ∼10 and decay time >20 s). The enhanced response speed is caused by the traps of the electron in TiO2 layer, which can accelerate the decay of current in the OFF state. The obtained results provide a new sight for the further development of the optoelectronic devices based on ZnO nanorod arrays in future. Graphical abstract: The photodetector based on TiO2 /ZnO nanorod arrays heterojunction structure has been prepared to construct ultraviolet photodetectors. And the influence of TiO2 layer for the performance of photodetector has been studied in detail. The obtained heterojunction photodetector has higher on/off ratio (>1000) and shorter rise/decay time (6.1/3.7 s) compared with that of the photodetector based on ZnO nanorod arrays. The enhanced response speed is caused by the traps of electron in TiO2 layer, which can accelerate the decay of current in the OFF state. The obtained results provide a new sight for the further development of the optoelectronic devices based on ZnO nanorod arrays in future. Image 1 Highlights: TiO2 /ZnO nanorod array heterojunction structure has been prepared. The photodetection performance of obtained PDs has been studied. Proper TiO2 layer can efficiently improve the response speed. TiO2 layer plays a role as an electron trap layer in the hybrid structure.